Diversity of woody plant nematodes in specially protected biocenosis of Zarafshan Mountain, Uzbekistan - SARDORBEK NARZULLAYEV; SARDOR KAMBAROV; UKTAM MIRZAEV; SHAHLO TURSUNOVA (Society for Indonesian Biodiversity, 2023)
Abstract. Narzullayev S, Kambarov S, Mirzaev U, Tursunova S. 2023. Diversity of woody plant nematodes in specially protected biocenosis of Zarafshan Mountain, Uzbekistan. Biodiversitas 24: 3145-3151. Very little information exists on nematodes' diversity and ecological characteristics in small artificial forests. This article provides information on the diversity of the nematode fauna, bioecological characteristics, and species distribution by biotopes of fruit trees growing in the biocenoses of the Omonkutan National Nature Park in the Western Zarafshan mountain range. As a result of the research, 62 species of nematodes were recorded in the nematode fauna of fruit trees. These species were analyzed taxonomically and ecologically. It was determined that the species in the fauna belong to two classes and five orders of the Nematoda type. They are divided into five large and several small groups according to their ecological characteristics. Among the ecological groups, omnivorous and plant-feeding nematodes are the dominant groups in terms of the number of species. The diversity of nematodes was high in the 0-15 and 15-30 cm soil layers. It turned out that the diversity in different biotopes is related to the ecological characteristics of nematodes. In particular, herbivorous nematodes accounted for 72.2% of nematodes in the root system. An increase in the diversity of nematodes was observed in the rhizosphere soil layers. A sharp increase in the number of species and individuals of omnivorous nematodes and bacteriotrophs was observed in the 0-15 cm soil layer, and this trend was also preserved in the 15-30 cm layer. The species richness and diversity (according to the Shannon and Simpson indices) were the lowest in vegetative parts of plants. As a result of the research, it became clear that the diversity of soil nematodes is completely dependent on their trophic characteristics.